The Routledge Handbook to Global Political Economy Conversations and Inquiries. - Vivares, Ernesto (Taylor & Francis Group, 2020)
"This handbook provides a comprehensive guide to how Global Political Economy (GPE) is conceptualized and researched around the world. Including contributions that range from traditional International Political Economy to GPE approaches, the book gathers the investigations, perspectives and innovative research from all over the world"--.